ALAT UKUR KESEHATAN PARU-PARU - Wulandari, Niki; Sindi Anggira; Ocsirendi; Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
In an effort to improve the accessibility andaccuracy of lung health monitoring, we developed aspirometry-based lung health device using theVLX5LOX distance sensor and Internet of Things (IoT)technology with the ESP 32 module. Spirometry is astandard method for measuring lung capacity andfunction. The VLX5LOX sensor can measure airflow speed using Time-of-Flight (ToF) technology and send real-time data to the ESP 32 module, which processes and transmits the data to an application. The implementation of IoT technology also allows forcloud data storage for further analysis, especially forpatients with poor lung health conditions. Test resultsshow that this device can provide measurementsconsistent with conventional spirometry methods, with the added advantages of better portability and data accessibility. The use of the VLX5LOX sensor and ESP32 in medical applications demonstrates great potential in developing innovative and affordablehealthcare devices.